The problem of bilingualism and tolerance in the multiethnic regional community. - M. Shakhbanova, Madina (2018)
The modern Russian regional society is multicultural and bilingual (multilingual) to make difficulties for mutual contacts of multilingual peoples. The problem of overcoming language barriers in a multi-ethnic regional community is in want of state support and special legal regulation. One of the best ways to solve this problem is bilingualism. Bilingualism is the possession of two languages - mother language and nationwide language (the so-called intermediary language). The choice of the language-mediator is determined by the socio-political, socio-historical and socio-economic conditions of life of a particular ethno-lingual education. The Russian language is the state language of the Russian society. The representatives of different nationalities enter into language contacts with each other through the Russian language. The Russian language serves as an intermediate language in the conditions of a multinational state. However, the uniqueness of any ethnic formation is manifested through language. Therefore the development of guarantees of linguistic rights is actually. Further we should be solving a bilingualism problem at the level of laws on languages adopted in the republics that make up the Russian Federation.